1979
DOI: 10.1530/jrf.0.0570245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium and potassium concentrations and pH on the maintenance of motility of rabbit and rat epididymal spermatozoa

Abstract: Spermatozoa were collected from the caput and cauda epididymidis of rabbits and rats and diluted in Hank's solution containing BSA, with various concentrations of Na+ and K+. Ionic strength and osmolarity were kept constant. Motility was assessed at various intervals during incubation at 25 degrees C. In the pH range 7.05--7.20, the motility of rabbit spermatozoa was not affected by changes in the ratio of K+ to Na+. Similarly, the motility of rat cauda spermatozoa was not altered, but that of caput spermatozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…There appears to be an association between high K+ levels in the epididymal plasma and inhibited epididymal sperm movement. Potassium concentrations much higher than those in blood plasma have been reported in the caput and/or cauda fluids of the hamster (39-3 mM; Jessee & Howards, 1976), the elephant (64-8 mM; Jones, 1980), the bull (43-7 mM; Wales, Wallace & White, 1966), the rat (54 mM; Pholpramool & Chaturapanich, 1979) and the rabbit (24-8 mM in the cauda; Jones & Glover, 1973). Boender (1976) showed that boar sperm motility was depressed in media with 45-135 mM-K + and that the motility was restored by washing the same spermatozoa in a medium containing 5 mM-K +.…”
Section: Analysis Of Sperm Movement Characteristics From Video Recordmentioning
confidence: 95%
“…There appears to be an association between high K+ levels in the epididymal plasma and inhibited epididymal sperm movement. Potassium concentrations much higher than those in blood plasma have been reported in the caput and/or cauda fluids of the hamster (39-3 mM; Jessee & Howards, 1976), the elephant (64-8 mM; Jones, 1980), the bull (43-7 mM; Wales, Wallace & White, 1966), the rat (54 mM; Pholpramool & Chaturapanich, 1979) and the rabbit (24-8 mM in the cauda; Jones & Glover, 1973). Boender (1976) showed that boar sperm motility was depressed in media with 45-135 mM-K + and that the motility was restored by washing the same spermatozoa in a medium containing 5 mM-K +.…”
Section: Analysis Of Sperm Movement Characteristics From Video Recordmentioning
confidence: 95%
“…However, involvement of other ion translocating systems, such as the ATP-dependent proton pump reportedly present in hamster sperm (22), must be considered. Consideration also must be given to reported differences between mammalian species in the response of sperm motility to variation of media pH and Na' and K+ concentrations (23).…”
mentioning
confidence: 99%
“…Pyknotic or shed epithelial cells of the epididymis and abnormal values of pH, osmotic pressure, and Na + 路K + concentrations in seminal plasma have been reported to be associated with the production of sperm with abnormal motility and morphology [7,13,14,30,32]. There is a report [11] on dogs stating that the epididymis and the proximal portion of the vas deferens are not only passage way for spermatozoa but accessory reproductive organs of spermatozoal maturation and storage.…”
Section: Discussionmentioning
confidence: 99%